(untitled) (PJDOL, 2023)
The purpose of this study is to analyze critically the two main categories of teachers’ unions as progressive and aggressive teachers’ unions and their positive and negative effects on students’ achievements at secondary school level. The researcher therefore determined to find out the exact roleof teachers’ unions